From kinetics to systems models: A critical review of heterotrophic nitrification-aerobic denitrification modeling for wastewater treatment - Huizhou Yuan; Chengmin Luo; Yaxin Zhang; Yurong Gu; Zhao Song; Liao Ouyang; Xiaoming Liu (Journal of Environmental Chemical Engineering, 2026)

Biochar mitigates nitrogen deposition-induced enhancement of soil N2O emissions in a subtropical forest - Jiashu Zhou; Manuel Delgado-Baquerizo; Tony Vancov; Yurong Liu; Xuhui Zhou; Ji Chen; Yunying Fang; Shuokang Liu; Bing Yu; Guomo Zhou; Baojing Gu; Jason C. White; et al. (Biology and Fertility of Soils, 2026)

From laboratory to field: Temperature rise triggers increased release and toxicity of microcystins in Microcystis aeruginosa - Shihao Wang; Yurong Gu; Weilu Li; Qingju Xue; Xinfeng Cheng; Chen Cheng; Liqiang Xie (Harmful Algae, 2026)

Sulfite-synergized VUV photolytic decomposition of metformin: A combined experimental and theoretical study - Yurong Gu; Zijun Dong; Qi Han; Liao Ouyang; Yihua Chen (Journal of Water Process Engineering, 2025)

ACSL4 accelerates osteosarcoma progression via modulating TGF-β/Smad2 signaling pathway - Xiaofeng Li; Qianfen Chen; Duo Zhao; Jianshi Tan; Rongbo Liao; Yurong Gu; Jinwei Zhu; Huying Zhang; Jian Xie; Lu Chen (Molecular and Cellular Biochemistry, 2025)
Osteosarcoma (OS) is a malignant bone sarcoma arising from mesenchymal stem cells. The biological role of Acyl-CoA synthetase long-chain family member 4 (ACSL4), recently identified as an oncogene in numerous tumor types, remains largely unclear in OS. In this study, we investigated the expression of ACSL4 in OS tissues using immunohistochemistry staining (IHC) staining of a human tissue microarray and in OS cells by qPCR assay. Our findings revealed a significant up-regulation of ACSL4 in both OS tissues and cells. To further understand its biological effects, we conducted a series of loss-of-function experiments using ACSL4-depleted MNNG/HOS and U-2OS cell lines, focusing on OS cell proliferation, migration, and apoptosis in vitro. Our results demonstrated that ACSL4 knockdown remarkably suppressed OS cell proliferation, arrested cells in the G2 phase, induced cell apoptosis, and inhibited cell migration. Additionally, a subcutaneous xenograft mice model was established to validate the in vivo impact of ACSL4, revealing ACSL4 silencing impaired tumor growth in the OS xenograft mice. Additionally, we discovered that ACSL4 could regulate the phosphorylation level of Smad2 through cooperative interactions, and treatment with a TGF-β inhibitor weakened the promoting effects of ACSL4 overexpression. In short, ACSL4 regulated OS progression by modulating TGF-β/Smad2 signaling pathway. These findings underscore ACSL4 as a promising therapeutic target for OS patients and contribute novel insights into the pathogenesis of OS. Graphical abstract

Fe2+-NTA synergized UV254 photolytic defluorination of perfluorooctane sulfonate (PFOS): Enhancing through intramolecular electron density perturbation via electron acquisition - Yihua Chen; Jiaxin Zhu; Hang Ma; Yurong Gu; Tongzhou Liu (Water Research, 2024)

Entrepreneurship in a time of social justice advocacy Entrepreneurship in a time of social justice advocacy , by James O. Fiet, Cham, Palgrave Macmillan, 2023, XV + 319 pp., $119.00 (eBook), ISBN 9783031354632 - Yurong Gu (The Social Science Journal, 2024)

Achieving high-rate and long-life Zn metal anodes via constructing interfacial gradient heterostructure - Yilun Ren; Biao Wang; Shaozhong Chang; Hao Wu; Yujie Ma; Fengqi Li; Cong Wang; Jian Gu; Yurong Yang; Shaochun Tang; Xiangkang Meng (Chemical Engineering Journal, 2024)

Changes in microcystin concentration in Lake Taihu, 13 years (2007–2020) after the 2007 drinking water crisis - Kaiye Zhang; Yurong Gu; Chen Cheng; Qingju Xue; Liqiang Xie (Environmental Research, 2024)

Participatory research and planning in practice - Yurong Gu (The Social Science Journal, 2023)

Kaempferol attenuates spinal cord injury by interfering inflammatory and oxidative stress by targeting the p53 protein: a molecular docking analysis - Lu Chen; Kai Cao; Yurong Gu; Chao Luo; Wei Mao; Weijun Zhou; Jinwei Zhu; Huying Zhang (Molecular & Cellular Toxicology, 2021)

Occurrence and risk assessment of microcystin and its relationship with environmental factors in lakes of the eastern plain ecoregion, China - Xiang Wan; Alan D. Steinman; Yurong Gu; Guangwei Zhu; Xiubo Shu; Qingju Xue; Wei Zou; Liqiang Xie (Environmental Science and Pollution Research, 2020)

Rapid and high-capacity adsorption of PFOS and PFOA by regenerable ammoniated magnetic particle - Tongzhou Liu; Yurong Gu; Ding Yu Xing; Wenyi Dong; Xiuwei Wu (Environmental Science and Pollution Research, 2018)

Arctigenin Suppress Th17 Cells and Ameliorates Experimental Autoimmune Encephalomyelitis Through AMPK and PPAR-γ/ROR-γt Signaling - Wen Li; Zhihui Zhang; Kai Zhang; Zhenyi Xue; Yan Li; Zimu Zhang; Lijuan Zhang; Chao Gu; Qi Zhang; Junwei Hao; Yurong Da; Zhi Yao; et al. (Molecular Neurobiology, 2016)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)